Família e habilidades socioemocionais: um estudo sobre a pessoa com deficiência em um curso de licenciatura em Biologia - Andrade, Joanna Angélica Melo de (2018)
Inclusive Education refers to the responsibility of the government and educational institutions of each country for the training and qualification of children and young people with disabilities, respecting the different types of differences. In this process of inclusion, two factors are important in addition to government actions: 1) the students' socio-emotional abilities (HSE), which will guarantee possibilities for inclusive innovation; and 2) the family, which plays an important role, the first interpersonal relationships and therefore where learning begins. HSE, when conducted properly, prepares the individual to seek what he desires, to solve daily situations, to discern behaviors and decisions, to establish goals, among other positions that collaborate for his personal growth, as well as his community. However, sometimes, in order to protect and care for the disabled, the family eventually creates impasses that hinder the development of certain skills and abilities important to life in society. In view of the above, we outline the general objective of identifying and describing the HSE of a licentiate with a disability in the biology course at the Federal University of Sergipe (UFS), understanding possible influences of the student's family in the construction of these skills. This is a research of exploratory nature, with qualitative approach performed through the single case study method. It takes place in the Biology Department (DBI) of UFS and as subjects of the research we have a disabled student with proper enrollment, a relative of the student (mother), a teacher in the course and the interpreter of Brazilian Language of Signals (LIBRAS), conferring a total of four subjects. For the data collection we used the semi-structured interview and for the analysis of the same, we adopted the Discursive Textual Analysis proposed in Moraes and Galiazzi (2014). The results indicate that the family of the licensee consulted acts to balance their influences between the incentive and the overprotection, and there are also reports of some scenes of prejudice, coming from relatives outside the family nucleus. Among her relatives, her mother seems to be the greatest motivator, and this can be one of the factors that contributes to the autonomy of the student throughout the process of inclusion. As for inclusion in the university, the interviewees report some difficulties, which become barriers, such as the prejudice and resistance of some colleagues and teachers throughout the course, however these barriers were and are being transposed by the student, and to this we can relate some HSE identified, such as autonomy, self-regulation, perseverance, organization, self-control and responsibility, which have been and are being developed both due to the influence of the family context and the academic life itself. We consider, therefore, that the family exerts influence in the construction of HSE of the licensee, and that these HSE are closely linked to the development of the student along the process of inclusion, and later formation.